PENGARUH PENGUMUMAN PERINGKAT SUKUK TERHADAP REAKSI PASAR - Srianingsih, Srianingsih; Khoiruddin, Moh. (Management Analysis Journal, 2015)
TheÂ purpose of this research is to explain the effect of sukuk rating announcement to market reaction. The population in this study is all of sukuk rating announcement of the companies that launch sukuk and stock during the year 2010-2014. The sample selected based on purposive sampling is 55 announcements. This study is an event study research using market adjusted model with 21 days of windows period (t-10 to t+10). The data used in this research is daily closing price that is collected by the documentation method. Analysis methods used in this research are normality test, one-sample t-test, and paired t-test. The results of this study find that there are significant sukuk rating announcement to the market reaction during 2 days that are onÂ  t+2 the significant is 5% and on t+3 the significant is 10%. The market reaction does not indicate significance difference between the return before and after the announcement. Market Efficiency happened is a semi-strong form because the investors are still enjoying the abnormal return for 2 days